Porous silicon composite metal and preparation method and application thereof
By using the co-precipitation method in a liquid phase environment, the mechanical integrity damage and battery caused by volume changes of silicon negative electrode materials are solved by thermal reduction. Capacity attenuation problem, the negative electrode material of lithium-ion battery with high reversible capacity and cycle stability is achieved.
Patent Information
- Application Number
- CN202411624033.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-14
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
Silicon negative electrode materials are damaged by volume changes in lithium-ion batteries and attenuated by battery capacity. The existing composite methods are complex and costly.
The metal is uniformly compounded with porous silicon by using a co-precipitation method in a liquid phase environment, and a new negative electrode material inlaid with metal in a porous silicon-based framework is formed by thermal reduction.
It realizes high reversible capacity, excellent cycle stability and low cost preparation of porous silicon composite metal materials, which is suitable for large-scale production.
Smart Images

Figure CN119480993A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of silicon composite materials, and in particular to a porous silicon composite metal and a preparation method and application thereof. Background Art
[0002] Improving the energy density and power density of lithium-ion batteries is a key problem that needs to be solved urgently in the field of lithium batteries. Graphite material is the most commonly used negative electrode material for commercial lithium-ion batteries. However, the theoretical specific capacity of graphite material is only 372mAh / g, which limits the development of high-energy lithium-ion batteries. Therefore, the design and development of negative electrode materials with high-capacity properties is of great significance to the development of new energy vehicles and large-scale energy storage batteries. The theoretical specific capacity of silicon negative electrode material is nearly 10 times higher than that of graphite, and it has the characteristics of moderate charging and discharging platform and abundant resources. It is one of the most promising negative electrode materials for the next generation of high-performance lithium-ion batteries and has broad market prospects.
[0003] However, the industrial application of silicon negative electrode materials still faces very severe challenges, because silicon undergoes a huge volume change (>300%) during the process of lithium extraction / insertion, which not only causes the cracking and crushing of silicon particles and the loss of electrical contact of the active material, but also destroys the mechanical integrity of the electrode. At the same time, the solid electrolyte interface film on the silicon surface is continuously generated and reorganized, which ultimately leads to rapid decay of the battery capacity. In order to solve the above problems, the composite of silicon and conductive materials such as metal particles has been proven to improve the conductivity of silicon electrodes and buffer the volume change of silicon during the cycle, thereby significantly enhancing the electrochemical performance. At present, the more effective methods for alloying silicon with metals are mostly electrothermal melting, magnetron sputtering, hot pressing, etc. These methods are complex and have high requirements for instruments and equipment. Therefore, it is of great significance to explore simpler and more effective design strategies. Summary of the invention
[0004] In order to solve the above technical problems, the purpose of the present invention is to provide a porous silicon composite metal and its preparation method and application, to provide a porous silicon-modified material, to fill the porous silicon with metal in situ, and to use it as a negative electrode material for lithium-ion batteries, providing a new design idea for silicon composite metal materials.
[0005] The above object of the present invention is achieved through the following technical solutions:
[0006] The first aspect of the present invention provides a method for preparing a porous silicon composite metal, characterized in that it comprises the following steps:
[0007] (1) dissolving silicate in water and adjusting the pH value to a strongly acidic state to obtain a silicate solution;
[0008] (2) adding a transition metal salt to the silicate solution obtained in step (1), adjusting the pH value to a weakly acidic state, causing a coprecipitation reaction, and obtaining a coprecipitate; the molar ratio of the silicate in step (1) to the transition metal salt in step (2) is (93-97):(3-7);
[0009] (3) Under an inert atmosphere, the coprecipitate obtained in step (2) is subjected to a reduction treatment to obtain the porous silicon composite metal.
[0010] The present invention uses a low-cost silicon source to achieve uniform mixing with metal materials in a liquid phase environment, and cleverly composites the metal into the porous silicon by adjusting the pH value, which can not only limit the volume expansion of silicon particles and improve the conductivity of silicon materials, but also construct a stable solid electrolyte interface film. The prepared porous silicon composite metal has excellent reversible capacity, rate performance and cycle stability when used as a negative electrode material for lithium-ion batteries, and has important development and utilization value. In addition, the preparation method provided by the present invention is simple to operate, has low requirements on instruments and equipment, and has great advantages over traditional processes.
[0011] Furthermore, in step (1), the silicate may be sodium silicate, potassium silicate, lithium silicate, etc.
[0012] Furthermore, in step (1), the pH value is 1.8-2.2, preferably 2.
[0013] Furthermore, in step (1), an organic acid may be used to adjust the pH value, and the organic acid is preferably formic acid.
[0014] Furthermore, in step (2), the transition metal salt is selected from one or more of tin salts, silver salts, chromium salts, cobalt salts, nickel salts, copper salts and iron salts.
[0015] Furthermore, in step (2), the transition metal salt is selected from one or more of nitrates, chlorides and fluorides.
[0016] Furthermore, in step (2), the pH value is 5.8-6, preferably 5.9.
[0017] Furthermore, in step (2), the pH value is adjusted using a base, and the base can be a base soluble in deionized water, preferably sodium hydroxide.
[0018] Furthermore, in step (2), the coprecipitation reaction time is 1-2h.
[0019] Furthermore, the molar ratio of the silicate in step (1) to the transition metal salt in step (2) is preferably 95:5.
[0020] In a specific embodiment, a transition metal salt is added to a silicate solution, stirred for 2-8 hours, and the pH value is adjusted to 5.8-6 to cause co-precipitation to obtain a co-precipitate.
[0021] Furthermore, in step (3), the specific method of the reduction treatment is: mixing the coprecipitate with a reducing agent, and performing a heat treatment at 650-700° C. in an inert atmosphere.
[0022] Furthermore, the reducing agent is magnesium powder.
[0023] Furthermore, hydrogen may be added into the inert atmosphere, and the volume ratio of the inert gas to hydrogen is 95:5.
[0024] Furthermore, in step (3), before the reduction treatment, the coprecipitate is further subjected to the steps of centrifugal separation and dehydration and drying.
[0025] Furthermore, in step (3), the step of washing the product is also included after the reduction treatment.
[0026] In a specific embodiment, the coprecipitate is centrifuged and dehydrated and dried, then mixed with magnesium powder, and heat treated at 650-700° C. in an argon-hydrogen atmosphere. The obtained powder is washed with acid and water to obtain the porous silicon composite metal.
[0027] The second aspect of the present invention provides a porous silicon composite metal prepared by the method described in the first aspect.
[0028] The porous silicon composite metal prepared by the invention is a material in which metal is embedded in a porous silicon-based skeleton.
[0029] The third aspect of the present invention provides a use of the porous silicon composite metal described in the second aspect in the preparation of a lithium ion battery.
[0030] A fourth aspect of the present invention provides a negative electrode material for a lithium ion battery, wherein the negative electrode material for a lithium ion battery comprises the porous silicon composite metal described in the second aspect, a conductive agent and a binder.
[0031] In a specific embodiment, porous silicon composite metal, conductive agent and binder are dissolved in water to prepare slurry, which is then coated, dried, pressed and sliced, and then vacuum dried at 100-140° C. to obtain a lithium-ion battery silicon-based negative electrode sheet.
[0032] Beneficial effects of the present invention:
[0033] The present invention provides a design concept for porous silicon composite metal, innovatively realizes uniform composite by co-precipitation method in liquid environment, and then forms a new type of negative electrode material in which metal is embedded in a porous silicon-based skeleton by thermal reduction method, thereby obtaining a silicon negative electrode material with high reversible capacity and excellent cycle stability.
[0034] The porous silicon composite metal prepared by embedding metal on a porous silicon-based skeleton in the present invention has the following advantages when used as a negative electrode material for lithium-ion batteries: first, the stability of the porous structure is enhanced, which can better adapt to the volume change of silicon during the charging and discharging process; second, the electronic / ionic conductivity of the silicon-based negative electrode can be greatly enhanced, polarization can be reduced, and the internal resistance of the battery can be reduced; third, the formation of a solid electrolyte interface film rich in LiF can be promoted, and the continuous consumption of the electrolyte and the continuous corrosion reaction of the silicon material can be inhibited.
[0035] The preparation process of the invention is simple, low in cost, low in requirements for instruments and equipment, non-toxic and harmless, suitable for large-scale production, and has broad application prospects and important application value. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 Scanning electron microscope images of the porous silicon composite tin-silver alloy prepared in Example 1 and the porous silicon material prepared in Comparative Example 1.
[0037] Figure 2 X-ray diffraction patterns of the porous silicon composite tin-silver alloy prepared in Example 1 and the porous silicon material prepared in Comparative Example 1.
[0038] Figure 3 It is a performance comparison chart of the first charge and discharge curves of the batteries assembled in Example 1 and Comparative Example 1.
[0039] Figure 4 It is a comparison chart of the long-term cycle performance of the batteries assembled in Example 1 and Comparative Example 1.
[0040] Figure 5 It is a comparison chart of the rate charge and discharge performance of the batteries assembled in Example 1 and Comparative Example 1.
[0041] Figure 6 This is a comparison chart of the impedance performance of the batteries assembled in Example 1 and Comparative Example 1.
[0042] Figure 7 It is a comparison chart of the long-term cycle performance of the batteries assembled in Example 8 and Comparative Examples 1-3. DETAILED DESCRIPTION
[0043] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0044] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments so that those skilled in the art can better understand the present invention and implement it, but the embodiments are not intended to limit the present invention.
[0045] Unless otherwise specified, the experimental methods used in the following examples are all conventional methods, and the materials, reagents, etc. used are all available from commercial sources unless otherwise specified.
[0046] Example 1
[0047] A method for preparing a porous silicon composite tin-silver alloy comprises the following steps:
[0048] (1) dissolving 1.12 g of sodium silicate in deionized water and adjusting the pH value to 2 to obtain a sodium silicate solution;
[0049] (2) adding 0.047 g of stannous fluoride and 0.034 g of silver nitrate (the molar ratio of sodium silicate, stannous fluoride and silver nitrate is 95:3:2) to the sodium silicate solution in sequence, stirring for 5 h, adjusting the pH value to 5.9, and standing for 1 h to allow a coprecipitation reaction to occur, thereby obtaining a coprecipitate;
[0050] (3) The coprecipitate was centrifuged, the precipitate was dehydrated and dried, and then mixed with 0.5 g of magnesium powder, and heat-treated at 650° C. in an argon-hydrogen atmosphere. The obtained powder was acid-washed twice, washed with deionized water five times, and washed with anhydrous ethanol once, and then dried in a vacuum oven at 60° C. overnight to obtain a porous silicon composite tin-silver alloy.
[0051] Example 2
[0052] A method for preparing a porous silicon composite tin-copper alloy is basically the same as that of Example 1, except that in step (2), 0.034 g of silver nitrate is replaced by 0.037 g of copper nitrate (the molar ratio of sodium silicate, stannous fluoride and copper nitrate is 95:3:2).
[0053] Example 3
[0054] A method for preparing a porous silicon composite tin-chromium alloy is basically the same as that of Example 1, except that in step (2), 0.034 g of silver nitrate is replaced by 0.047 g of chromium nitrate (the molar ratio of sodium silicate, stannous fluoride and chromium nitrate is 95:3:2).
[0055] Example 4
[0056] A method for preparing a porous silicon composite tin-cobalt alloy is basically the same as that of Example 1, except that in step (2), 0.034 g of silver nitrate is replaced by 0.036 g of cobalt nitrate (the molar ratio of sodium silicate, stannous fluoride and cobalt nitrate is 95:3:2).
[0057] Example 5
[0058] A method for preparing a porous silicon composite tin-nickel alloy is basically the same as that of Example 1, except that in step (2), 0.034 g of silver nitrate is replaced by 0.036 g of nickel nitrate (the molar ratio of sodium silicate, stannous fluoride and nickel nitrate is 95:3:2).
[0059] Example 6
[0060] A method for preparing a porous silicon composite nickel-iron alloy is basically the same as that of Example 1, except that in step (2), 0.047 g of stannous fluoride is replaced by 0.054 g of nickel nitrate, and 0.034 g of silver nitrate is replaced by 0.048 g of ferric nitrate (the molar ratio of sodium silicate, nickel nitrate and ferric nitrate is 95:3:2).
[0061] Example 7
[0062] A method for preparing a porous silicon composite silver-copper alloy is basically the same as that of Example 1, except that in step (2), 0.047 g of stannous fluoride is replaced by 0.05 g of silver nitrate, and 0.034 g of silver nitrate is replaced by 0.037 g of copper nitrate (the molar ratio of sodium silicate, silver nitrate and copper nitrate is 95:3:2).
[0063] Example 8
[0064] A method for preparing porous silicon composite copper is basically the same as that of Example 1, except that in step (2), 0.047 g of stannous fluoride and 0.034 g of silver nitrate are replaced by 0.094 g of copper nitrate (the molar ratio of sodium silicate to copper nitrate is 95:5).
[0065] Comparative Example 1
[0066] A method for preparing a porous silicon material without metal modification comprises the following steps:
[0067] (1) Dissolve 1.12 g of sodium silicate in deionized water, adjust the pH to 2, stir for 5 h, adjust the pH to 5.9, and let stand for 1 h;
[0068] (3) The product obtained in step (1) is centrifuged, the precipitate is dehydrated and dried, and then mixed with 0.5 g of magnesium powder, and heat-treated at 650° C. in an argon-hydrogen atmosphere. The obtained powder is acid-washed twice, washed with deionized water five times, and washed with anhydrous ethanol once, and then placed in a vacuum oven at 60° C. to dry overnight to obtain a porous silicon material.
[0069] Comparative Example 2
[0070] A method for preparing porous silicon composite copper is basically the same as that of Example 1, except that in step (2), 0.047 g of stannous fluoride and 0.034 g of silver nitrate are replaced by 0.188 g of copper nitrate (the molar ratio of sodium silicate to copper nitrate is 9:1).
[0071] Comparative Example 3
[0072] A method for preparing porous silicon composite copper is basically the same as that of Example 1, except that in step (2), 0.047 g of stannous fluoride and 0.034 g of silver nitrate are replaced by 0.94 g of copper nitrate (the molar ratio of sodium silicate to copper nitrate is 1:1).
[0073] Figure 1 The scanning electron microscope images of the porous silicon composite tin-silver alloy prepared in Example 1 and the porous silicon material prepared in Comparative Example 1 are shown in FIG. Figure 1 It can be seen that the porous silicon material prepared in Comparative Example 1 is a porous structure with a honeycomb shape and a radius of about 150um. The porous structure in the porous silicon composite tin-silver alloy prepared in Example 1 is partially filled, indicating that the Sn / Ag particles are embedded in the silicon bulk phase to form a silicon-based metal skeleton. The incorporation of Sn / Ag fills the original holes and greatly improves the mechanical strength of the material.
[0074] Figure 2 The X-ray diffraction patterns of the porous silicon composite tin-silver alloy prepared in Example 1 and the porous silicon material prepared in Comparative Example 1 show that Example 1 has three obvious characteristic peaks between 34° and 40°, and the substance they represent is Ag3Sn, indicating that the particles embedded in the silicon bulk phase are tin-silver alloy.
[0075] Application Examples
[0076] The porous silicon material, conductive carbon black and sodium alginate binder of the embodiment and comparative example were dissolved in water at a mass ratio of 7:1:2 to prepare a slurry, which was coated and dried, pressed and sliced, and then vacuum dried at 120° C. to obtain a lithium-ion battery silicon-based negative electrode sheet.
[0077] The C2032 button cell was assembled in a glove box. The assembly method was as follows: the positive electrode shell was placed flat on the insulating table with insulating tweezers, the negative electrode sheet was placed in the center of the positive electrode shell, 2 to 3 drops of electrolyte were added with a dropper, and then the diaphragm was placed flat on the upper layer of the negative electrode sheet, and then 2 drops of electrolyte were added. The lithium sheet, gasket, spring, and negative electrode shell were placed flat on the upper layer of the diaphragm with insulating tweezers in turn, and the lithium sheet was aligned with the negative electrode sheet on the other side of the diaphragm. Finally, the button cell was placed on the mold of the button cell sealing machine with the negative electrode side facing up with insulating tweezers, and the pressure (800Pa) was adjusted to press for 5s to complete the assembly of the button cell. Among them, the solvent of the electrolyte was composed of ethylene carbonate, diethyl carbonate, and dimethyl carbonate, with a volume ratio of 1:1:1, the solute was lithium hexafluorophosphate, the concentration was 1 mol / L, and the additive was 10% fluorinated ethylene carbonate by mass fraction; the specification model of the diaphragm was PPGM-2500-HC.
[0078] Test Case
[0079] The electrochemical performance test of the C2032 button battery assembled in the corresponding use case was carried out. It was first charged for 3 cycles with 0.05C current, and then for 5 cycles with 0.1C current. Then, the cycle performance test was carried out at 0.5C. The rate performance test of the material was carried out at different discharge rates. The test results are shown in Table 1:
[0080] Table 1
[0081]
[0082]
[0083] from Figure 3 and Figure 4 It can be seen that the first charge and discharge capacity and long-term cycle performance of the battery assembled in Example 1 are significantly improved compared with those in Comparative Example 1. The incorporation of tin / silver greatly improves the first reversible capacity and long-term cycle performance of the porous silicon negative electrode. After 100 cycles, the reversible capacity of the battery assembled in Example 1 is about 3 times that of Comparative Example 1, confirming the excellent electrochemical performance of the tin / silver filled porous silicon material. In addition, from Figure 5 It can be seen that the discharge capacity of the tin / silver filled porous silicon material at different rates is nearly 800 mAh / g higher than that of the unmodified porous silicon negative electrode in Comparative Example 1, showing excellent rate performance. Figure 6 It can be seen that the impedance of Example 1 is significantly lower than that of Comparative Example 1, which is consistent with its excellent rate performance.
[0084] From Table 1 and Figure 7 It can be seen that as the proportion of metal elements decreases, its reversible capacity and first coulombic efficiency are improved to a certain extent.
[0085] Obviously, the above embodiments of the present invention are only examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. Those skilled in the art should understand that other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a porous silicon composite metal, characterized in that: The following steps are involved: (1) dissolving silicate in water and adjusting the pH value to a strongly acidic state to obtain a silicate solution; (2) adding a transition metal salt to the silicate solution obtained in step (1), adjusting the pH value to a weakly acidic state, causing a coprecipitation reaction, and obtaining a coprecipitate; the molar ratio of the silicate in step (1) to the transition metal salt in step (2) is (93-97):(3-7); (3) Under an inert atmosphere, the coprecipitate obtained in step (2) is subjected to a reduction treatment to obtain the porous silicon composite metal.
2. The preparation method according to claim 1, characterized in that: In step (1), the pH value is 1.8-2.
2.
3. The preparation method according to claim 1, characterized in that: In step (2), the transition metal salt is selected from one or more of tin salts, silver salts, chromium salts, cobalt salts, nickel salts, copper salts and iron salts.
4. The preparation method according to claim 1 or 3, characterized in that: In step (2), the transition metal salt is selected from one or more of nitrates, chlorides and fluorides.
5. The preparation method according to claim 1, characterized in that: In step (2), the pH value is 5.8-6.
6. The preparation method according to claim 1, characterized in that: In step (2), the coprecipitation reaction time is 1-2h.
7. The preparation method according to claim 1, characterized in that: In step (3), the specific method of the reduction treatment is: mixing the coprecipitate with a reducing agent, and performing a heat treatment at 650-700° C. in an inert atmosphere.
8. A porous silicon composite metal prepared by the method according to any one of claims 1 to 7.
9. Use of the porous silicon composite metal according to claim 8 in the preparation of lithium ion batteries.
10. A negative electrode material for a lithium ion battery, characterized in that: The negative electrode material of the lithium-ion battery comprises the porous silicon composite metal according to claim 8, a conductive agent and a binder.
Citation Information
Patent Citations
Silicon-carbon composite material, preparation method and application of silicon-carbon composite material
CN105655555A
Method for preparing nanometer silicon based on introduction of metal into metallothermic reduction
CN106495161A
Sodium Transition Metal Silicate And Method Of Forming Same
CN107709237A
Metal compounding method of porous silicon-based negative electrode material and application of porous silicon-based negative electrode material in lithium ion battery
CN116544391A
Precipitation of metals
CN117337339A